Proceedings of the 2nd Unconventional Resources Technology Conference 2014
DOI: 10.15530/urtec-2014-1921520
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of CO2 Adsorption on Permeability Anisotropy in the Eagle Ford Shale

Abstract: The URTeC Technical Program Committee accepted this presentation on the basis of information contained in an abstract submitted by the author(s). The contents of this paper have not been reviewed by URTeC and URTeC does not warrant the accuracy, reliability, or timeliness of any information herein. All information is the responsibility of, and, is subject to corrections by the author(s). Any person or entity that relies on any information obtained from this paper does so at their own risk. The information here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…Pini et al 2009). A similar effect was reported by Al Ismail et al (2014), who reported a 10% decrease in layer-parallel shale permeability and a much larger, ~ 1 order of magnitude reduction in layer-perpendicular permeability, ascribed to CO 2 adsorption. However, since in our samples, the content of phases that may swell (smectite, organics) was minor, this is less likely to have been significant.…”
Section: Argon and Co 2 Permeabilitiessupporting
confidence: 82%
“…Pini et al 2009). A similar effect was reported by Al Ismail et al (2014), who reported a 10% decrease in layer-parallel shale permeability and a much larger, ~ 1 order of magnitude reduction in layer-perpendicular permeability, ascribed to CO 2 adsorption. However, since in our samples, the content of phases that may swell (smectite, organics) was minor, this is less likely to have been significant.…”
Section: Argon and Co 2 Permeabilitiessupporting
confidence: 82%
“…Permeability measurements follow the same experimental setup used by (Heller et al, 2014;Al Ismail et al, 2014). Samples were loaded inside a hydrostatic pressure vessel core holder connected to an isco 100DX syringe pump for confining pressure.…”
Section: Permeability Experimental Setupmentioning
confidence: 99%
“…Cheng et al [75] and Armitage et al [76] investigated the effects of permeability anisotropy on buoyancy driven CO 2 flow. Al Ismail et al [77] investigated the effects of CO 2 adsorption on permeability anisotropy. Taheri et al [78] made an attempt to investigate the effects of anisotropy and heterogeneity in both the horizontal and vertical directions of layering on the CO 2 dissolution in a saturated porous medium with brine using simulation methods.…”
Section: The Petrophysical and Mechanical Characteristics Of Shalementioning
confidence: 99%